Estratégias de enfrentamento e problemas comportamentais em crianças com câncer, na classe hospitalar - Hostert, Paula Coimbra da Costa Pereira (2010)
Hospitalization, especially in case of chronic diseases such as cancer, affects children's behavior and development. However, this can be managed through the child’s coping strategies (CS) and the conditions offered by the hospital, such as a hospital school (HS). This study analyzed the coping strategies (CS) of children with cancer, including their playing preferences and their relation with emotional and behavior problems, taking into account the role of hospital school (HS) attendance in managing these issues. Eighteen (18) children (aged between 6 and 12) with cancer participated in the study. They had been hospitalized for an average of 47 days and had been attending the hospital school of a public children's hospital. They responded to the Computerized Instrument for Assessing Coping Strategies (ACScomp) and the Computerized Instrument for Assessing Playing at the Hospital (APHcomp).Their caregivers responded to the Child Behavior Checklist (CBCL- 6 to 18 years old) and Rutter’s Child Behavior Scale- (CBS). Study 1 analyzed hospitalization coping strategies (CS), identifying distraction as the most frequent one, followed by rumination, problem solving and search for support. The most common behavior presented included: playing, talking, watching TV, taking medications, and studying. Study 2 analyzed playing preferences at the hospital and behavior and emotional problems of these children, identifying their favorite activities: drawing and watching TV. Most children presented behavior problems (94.4%) in the CBCL, and emotional problems (61.1%) in the ECI. In general, there was no significant relation between children’s disease and sociodemographic data; behavior and emotional problems; and coping strategies (CS) and playing preferences. These children presented coping strategies (EE) similar to those of children who did not attend hospital school (CH). These findings suggest that children suffer a significant impact during hospitalization. Therefore, they need help to create coping strategies (EE) that favor their development. This condition justifies the encouragement to playing in the hospital setting, since it plays its role as coping strategy and humanizer of child hospitalization.